Indicators for the total number of melanocytic naevi: an adjunct for screening campaigns. Observational study on 292 patients. (January 2014) - Echeverría, B.; Bulliard, J.‐L.; Guillén, C.; Nagore, E.
Summary Background The presence of multiple melanocytic naevi is a strong risk factor for melanoma. Use of the whole body naevus count to identify at‐risk patients is impractical. Objectives To (i) identify a valid anatomical predictor of total naevus count; (ii) determine the number of naevi that most accurately predict total naevus count above 25, 50 and 100; and (iii) evaluate determinants of multiple melanocytic naevi and atypical naevi. Methods Clinical data from 292 consecutive Spanish patients consulting for skin lesions requiring debriding were collected throughout 2009 and 2010. Correlations between site‐specific and whole body naevus counts were analysed. Cut‐offs to predict total naevus counts were determined using the area under the receiver operating characteristic curve. Results The studied population was young (median age 31 years, interquartile range 28–43). The naevus count on the right arm correlated best with the total nevus count (R2 0·80 for men, 0·86 for women). Presence of at least five naevi on the right arm was the strongest determinant of a total naevus count above 50 [odds ratio (OR) 34·4, 95% confidence interval (CI) 13·9–85·0] and of having at least one atypical naevus (OR 5·7, 95% CI 2·4–13·5). Cut‐off values of 6, 8 and 11 naevi on the right arm best predicted total naevus count above 25, 50 and 100, respectively. Conclusions Our results support the arm as a practical and reliable site to estimate the total naevus count when screening or phenotyping large populations. Threshold values for the number of naevi on the arm are proposed to help identify patients for melanoma screening.